Prevalence and influencing factors of psychological distress among nurses in sichuan, china during the COVID-19 outbreak: A cross-sectional study - Xie, Caixia; Zhang, Jia; Ping, Jia; Li, Xinyu; Lv, Yu; Liao, Limei (Frontiers in Psychiatry, 2022)
Background: The COVID-19 pandemic has spread across the world. Nurses have inevitably been influenced by it. Purpose: To investigate the prevalence and influencing factors of psychological distress among nurses in Sichuan, China over the COVID-19 outbreak. Methods: This study used a cross-sectional survey design. 1870 nurses who worked in COVID-19-designated hospitals participated in the study during the pandemic. Data was collected online between February 8 and February 13, 2020. Findings: 12% of nurses were found to experience psychological distress. The main influencing factors were personal precautionary measures at work, discomfort caused by protective equipment, perception of the hospital safety climate, coping style, and professional title. Conclusions: In the pandemic, wearing protective equipment correctly, a safe hospital climate, and positive coping style for nurses could be beneficial for nurses’ mental health. Nurse managers should take measures to build a safe hospital climate.